2012
DOI: 10.7314/apjcp.2012.13.6.2781
|View full text |Cite
|
Sign up to set email alerts
|

A Study on Community Perceptions of Common Cancers, Determinants of Community Behaviour and Program Implementation in New Delhi, India

Abstract: Assessment of perceptions of the community, the determinants and development of their behavior regarding common malignancies, helps in establishing evidence-based activities for prevention and early diagnosis of cancer. However information on this important aspect is lacking in our country. Qualitative methods were here used to obtain information through in depth interviews and Focus Group Discussions (FGDs) with all categories of identified stakeholders. Most were unaware of the activities of the cancer contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 28 publications
(30 reference statements)
0
4
0
Order By: Relevance
“…The rates of breast cancer have increased over the past two decades (Asnarulkhadi et al, 2012). The WHO estimates that by the year 2020, the number of cases of cancer will double in developing countries (Seth et al, 2012). In Iran also, statistics indicate a huge increase in incidence of this disease Among Iranian women and It includes 22.9 percentage of invasive cancers in women and 16 percent of all cancers (Sabokbar et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The rates of breast cancer have increased over the past two decades (Asnarulkhadi et al, 2012). The WHO estimates that by the year 2020, the number of cases of cancer will double in developing countries (Seth et al, 2012). In Iran also, statistics indicate a huge increase in incidence of this disease Among Iranian women and It includes 22.9 percentage of invasive cancers in women and 16 percent of all cancers (Sabokbar et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The psychological burden experienced by male partners during the disclosure of cervical cancer diagnostic results could be explained by limited awareness, negative attitudes, and perceptions of cancer in society. In many societies, cancer is perceived as a debilitating and life‐threatening condition, regardless of the type or stage at which it is revealed 35‐37 . This study also revealed that most of the individual participants and their societies believed that cervical cancer was incurable and meant an immense death.…”
Section: Discussionmentioning
confidence: 67%
“…In many societies, cancer is perceived as a debilitating and life-threatening condition, regardless of the type or stage at which it is revealed. [35][36][37] This study also revealed that most of the individual participants and their societies believed that cervical cancer was incurable and meant an immense death. It had been reported previously that the psychological burden on the cancer patient caregiver can worsen than that faced by the patients, especially when the disease advances and eventually reduces QoL.…”
Section: Reproductive Concernsmentioning
confidence: 68%
“…The incidence of breast cancer and its fatal effects are constantly on a rise across the globe 1 .Over the past twenty years ratio of breast cancer has increased and WHO in one of its reports has shown double the number of carcinoma breast cases in developing countries by year 2020 4 . Breast cancer is the most common cancer in Pakistani women, with approximately 1 in every 9 Pakistani women developing breast cancer at some stage of their 2 .In females breast cancer is the commonest (20.8%) in Khyber Pakhtunkhwa, followed by skin, ovary, oral carcinoma, esophagus and cervix 7. Majority of female breast cancer patients in Khyber Pakhtunkhwa presents with advanced disease and hence poor prognosis and outcome 5 . Risk factors of breast carcinoma include female gender, genetic mutations, positive family history, proliferative breast diseases, younger age at menarche, late menopause, 1st pregnancy at age older than 35, nulliparity, radiation exposure, exogenous hormone use, alcohol, high fat diet, sedentary life style and obesity 6 .…”
Section: Introductionmentioning
confidence: 99%